ADVANCING LEARNER AUTONOMY IN TEFL VIA COLLABORATIVE LEARNING - George Jacobs; Tan Hui Shan (University of Muhammadiyah Purwokerto, 2016)
Learner autonomy has been defined as 'a capacity to control important aspects of one's learning'(Benson, 2013, p. 852). In the teaching of additional languages, learner autonomy dates back at least to the 1970s. For instance, Trim, who was a leader in the teaching of additional languages in Europe, stated that a goal of language education was to: make the process of language learning more democratic by providing the con- ceptual tools for the planning, construction and conduct of courses closely geared to the needs, motivations and characteristics of the learner and enabling him [sic] so far as possible to steer and control his own progress. (1978, p. 1)